Representasi Makna Perpisahan pada Lirik Lagu “Give Me Five” Karya JKT48: Analisis Semiotika Ferdinand de Saussure - Gunadi, Dauhah Fitriyani (Jurnal Pendidikan Non formal, 2023)
This article contains the representation of the meaning of separation in the lyrics of the song "Give Me Five" by JKT48 (Fer-dinand de Saussure's semiotic study). The semiotic method that will be used in this research is semiotics from Saussure's thought. Saussure's theory explains that signs have interconnected elements, namely signifier and signified. This process connects the song lyrics with the real external world. The results of this research from the lyrics of the song "Give Me Five" by JKT48 have interrelated meanings containing the message that separation is not the end of everything. The meaning of separation contained in the lyrics of the song "Give Me Five" by JKT48 is very strong, because a person cannot avoid the word goodbye, besides that there is motivation to achieve another dream when the separation occurs. The data analysis technique used is analysis using Ferdinand de Saussure's semiotic theory. Saussure's theoretical model focuses more direct attention on the sign itself. In this research on the lyrics of the song "Give Me Five", the researcher makes an interpretation by dividing the entire song lyrics into several stanzas and then the stanzas will be analyzed using Saussure's semiotic theory.